ANALISIS KEBANGKRUTAN PADA PERUSAHAAN SUB SEKTOR RESTORAN YANG TERDAFTAR DI BEI PADA MASA SEBELUM HINGGA PANDEMI COVID-19 MENGGUNAKAN METODE ZMIJEWSKIE - Hidayat, Wastam Wahyu (Makro Jurnal Manajemen Dan Kewirausahaan, 2024)
This research aims to determine the level of bankruptcy in restaurant companies before the Covid-19 pandemic as measured using the Zmijewskie Z-Score method. This research is quantitative research with data on 4 companies listed on the Indonesian Stock Exchange for the 2019-2021 period. This research was assisted by the Microsoft Excel program. The results of the research show that the restaurant sub-sector companies listed on the Indonesia Stock Exchange for the 2019 period, because the score < 0, means that the companies entered the company did not go bankrupt, but in 2020 semester I and 2020 semester II x -score experienced a very significant decline from the previous period, this happened because net income, total assets and current liabilities decreased from the previous period. The highest level of accuracy with an accuracy value of 65% in bankruptcy predictions for 4 companies in the restaurant sub-sector for the 2019 - 2021 period, is because the bankruptcy prediction results from 20 samples of 13 samples are closest to the actual financial conditions seen from the real profits generated by the companies.